Modelagem numérica da transferência de calor no Ensaio Jominy - Nunura, César Rolando Nunura (2016)
His work considers the numerical simulation of the Jominy test, which evaluates the hardenability of steels, using as a solution the Finite Difference Method. Taking the initial and boundary conditions of the test and considering the heat transfer by conduction and forced convection, is solved numerically explicitly the differential equation that modeling the test, to obtain simulations of the thermal evolution or cooling curves at the specimen. Using the thermal profile obtained by the numerical solution is proposed a method for obtain the cooling rates and expressions that correlate hardness profile after the test [HRC = f (Cooling Rate)], and the numerical prediction of the final microstructures [Microstructure% = f (Cooling Rate)]. To validate the simulations were tested 02 steels: SAE 1060 and SAE 52100 according to ASTM A 255-07. These tests were instrumented with thermocouples for obtain the experimental thermal profile and compare with the simulated results. Hardness tests (HRC) were applied at the specimens for obtain the Jominy profile. Finally, analysis microscopy was applied to the specimens revealed the amounts of martensite, bainite, pearlite and ferrite present in the microstructure of the steel in function to the cooling rates. These microstructures validate the numerical results of [HRC = f (Cooling Rate)] and [% Microstructure = f (Cooling Rate)].